Fracture risk, underlying pathophysiology, and bone quality assessment in patients with Turner syndrome - Ikegawa, Kento; Hasegawa, Yukihiro (Frontiers in Endocrinology, 2022)
Turner syndrome (TS), the most common type of X chromosomal disorder, has various, clinical manifestations. Among these, primary hypogonadism, which may lead to osteoporosis, is a life-long health issue. A high prevalence of fractures associated with osteoporosis is a major problem in patients with TS, where it may be 1.4-2.2 times higher than in healthy individuals and increases with age. Among the risk factors associated with fractures in TS, hypogonadism is arguably the most important. Estrogen deficiency due to hypogonadism leads to low bone mineral density (BMD), resulting in a high prevalence of bone fractures. Estrogen replacement therapy (ERT) in patients with TS reportedly improved their BMD. However, other causes of low BMD may exist, given that this condition begins in the prepubertal period in patients with TS. Most previous studies have reported low BMD in patients with TS using dual-energy X-ray absorptiometry (DXA), but this method has some limitations. Areal BMD values assessed by DXA were influenced by bone size and short stature, resulting in an underestimation of BMD. Currently, volumetric BMD values may be accurately obtained using peripheral quantitative computed tomography (pQCT). pQCT, high-resolution pQCT, and the trabecular bone score can also be used to evaluate bone quality, including bone geometry and microarchitecture, in TS. The present review discusses the high fracture risk, role of estrogen deficiency in low BMD, advantages and disadvantages of various bone assessment methods, and characteristics of bone quality in TS.